Synergistic Effects of Carvacrol and Thymol on Docetaxel-Induced Cytotoxicity in the A549 Cell Line by Evaluating Cell Viability and Oxidative Stress - Mohammad Shokrzadeh; Mahboube Rahmati Kukandeh; Mohammad Karami; Samane Sadat Besharat (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: Docetaxel is an effective chemotherapy drug for treating lung cancer, but its side effects and cytotoxicity limit its use. Natural compounds like carvacrol and thymol, known for their anti-cancer and anti-inflammatory properties, have gained attention as adjunct agents to reduce toxicity and enhance the efficacy of chemotherapy drugs. This study aimed to investigate the impact of carvacrol and thymol on cell viability and function in A549 cancer cells exposed to docetaxel. Methods: This experimental study was conducted on the epithelial cell line derived from lung cancer tissue (A549), obtained from the Pasteur Institute of Iran at the Faculty of Pharmacy, Mazandaran University of Medical Sciences in the year 1042. In this research, A549 cells were pre-treated with various concentrations of carvacrol and thymol (5, 10, 20, 40, 80, 100, and 200 µg/mL) along with a cytotoxic dose of docetaxel (8.92 µg/mL) over a period of 48 hours. Cytotoxicity was assessed using the MTT assay. Additionally, the levels of reactive oxygen species (ROS) in cells were measured using the DA-DCFH reagent, and malondialdehyde (MDA) levels were determined using the thiobarbituric acid (TBA) reagent. Results: Carvacrol and thymol significantly reduced the cytotoxic effects of docetaxel at concentrations ranging from 5 to 200 µg/mL (P<0.05). The evaluation of cytotoxicity indicated that at a concentration of 200 µg/mL, carvacrol and thymol exhibited a more pronounced enhancing effect (98.11±1.64%) compared to the concentration of 5 µg/mL (54.64±2.03%). Furthermore, these compounds significantly mitigated the oxidative stress induced by docetaxel by decreasing the production of reactive oxygen species (ROS) and malondialdehyde (MDA) (P<0.05). Specifically, at the concentration of 200 µg/mL, the levels of ROS and MDA were (13.57±0.09%) and (0.55±0.003%), respectively, in contrast to the levels at 5 µg/mL, which were (20.50±0.59%) and (0.98±0.01%). This demonstrates a notable inhibitory effect on the growth of cancer cells by carvacrol and thymol. Conclusion: Carvacrol and thymol demonstrate high potential as compounds to improve cell function and reduce the cytotoxicity induced by docetaxel in A549 cancer cells. These findings suggest the potential enhancement of chemotherapy regimens for cancer treatment.